User’s Innovation and Human Values in the Health Systems - Echeverría, Javier (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
Innovations in the health sector policies have been based on the R+D, since the pharmacological companies have invested heavily in the R+D+i. However, the innovation studies have shown in recent years that user innovation has as much or more importance than innovation based on the I+D, as it had been claimed many years ago by von Hippel and his followers (1998, 2005). The British NESTA (National Endowment for Science, Technology and Arts) has published in 2011 a first study on innovation in health systems, which demonstrates that user’s innovation is also common in medicine. Based on this paradigm shift in the studies and policies of innovation, this article states that user’s innovation in the health systems aids to the advance of Medical Humanities, by promoting human and social values in medical practices.